Trends and collaborations in case-based learning for online health education: a bibliometric analysis (2014-2024) - Budiawan, Agung; Wirasti, Murti Kusuma; Kusumawardani, Dwi (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
Case-based learning is one of the interactive learning methods that uses real case scenarios or simulations to involve students in the active learning process. This study aims to map and analyze publication trends related to using case-based learning (CBL) in online health education from 2014–2024. This study focuses on publication trends and author collaborations without directly assessing the effectiveness of CBL. Using bibliometric analysis methods on data taken from the Scopus database, this study analyzes the frequency of publications, emerging topics, and collaboration networks between authors, with tools such as VOSviewer for visualization of collaboration maps and topic trends. The results show that publications on CBL have increased significantly since 2018, with a peak occurring between 2020 and 2023. This increase is closely related to changes in education policies during the COVID-19 pandemic, which have encouraged the adoption of interactive methods in distance learning, especially in the health sector. In addition, integrating educational technologies such as digital simulation platforms and artificial intelligence (AI) has strengthened the adoption of CBL in online environments. This study also found a collaboration network between authors with Al-Omran Mohammed as a central figure in international collaboration. These findings provide implications for educators, institutions, and policymakers to expand the application of CBL methods and train educators in designing effective case-based curricula.